2020
DOI: 10.1080/01490400.2020.1817201
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Social and Cultural Capitals for Immigrant Hosts of VFR Travellers

Abstract: The hosting of friends and relatives is an important and common experience. Hosting gives reason and opportunity for residents to explore their community while spending time with guests. For newcomers, hosting brings additional significance due to their relative isolation from traditional social networks and comparative unfamiliarity with the community. This narrative inquiry examines immigrants' experiences of hosting friends and relatives using Bourdieu's theories of social and cultural capital. Findings sug… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 105 publications
0
23
0
Order By: Relevance
“…These researchers called for a comparative analysis of hosts from different origins for both theoretical, management and marketing implications. Griffin and Glover (2020) and Griffin and Guttentag (2020) revealed that hosting VFR visitors creates an experiential and relational context of personal refreshment, resource exchange and capital generation that enhance hosts’ habitus. Hosts would have a changing impact on their personal identity, sense of accomplishments, level of familiarity with the new culture and destinations that may contribute to further integration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These researchers called for a comparative analysis of hosts from different origins for both theoretical, management and marketing implications. Griffin and Glover (2020) and Griffin and Guttentag (2020) revealed that hosting VFR visitors creates an experiential and relational context of personal refreshment, resource exchange and capital generation that enhance hosts’ habitus. Hosts would have a changing impact on their personal identity, sense of accomplishments, level of familiarity with the new culture and destinations that may contribute to further integration.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the discussion with the respondents, it has been found that before the outbreak of the COVID-19 pandemic these Bangladeshi immigrants in GTA used to host friends and relatives every weekend or twice a week as they claimed that hosting was an integral part of their life (Griffin & Glover, 2020). Visitors came from the GTA or other parts of Canada regularly.…”
Section: Discussionmentioning
confidence: 99%
“…It has been evident that the interconnection between tourism-migration includes tourismrelated experiences that involve prior personal relationships (Griffin, 2013b(Griffin, , 2017Palovic et al, 2014) between hosts and guests. Most of the past research in VFR travel that analyzed the relationship between tourism and migration addressed macro-level flows (Dwyer et al, 2014;Etzo et al, 2014;King & Dwyer, 2015;Massidda et al, 2015) and ignored the interpersonal relationships as a cause for shaping the ties among people (Griffin & Glover, 2020). Considering such influence of the immigrants, travel agencies are suggested to maintain a strong connection with the ethnic communities to understand their culture and language to promote local activities and other facilities (Shani & Uriely, 2012).…”
Section: Migration and Vfr Tourismmentioning
confidence: 99%
“…A VFR host can be defined as a resident who engages in some face-to-face interaction with a visitor within his or her home community, with whom the host has an existing relationship (Griffin & Glover, 2020). Yousuf and Backer (2017) defined a VFR host as someone who has had friends and/or relatives visited and stayed at least one night in the destination.…”
Section: Definition Of Hostingmentioning
confidence: 99%
See 1 more Smart Citation